The prevalence of intracranial stenosis in patients at low and moderate risk of stroke. (August 2019) - Chen, Hong-xiu; Wang, Li-juan; Yang, Yi; Yue, Fei-xue; Chen, Li-min; Xing, Ying-qi
Background: Previous studies assessing the risk of stroke in the general population performed screening with Doppler ultrasonography only for high-risk patients and neglected low- and moderate-risk patients. The aims of this study were to explore the current prevalence of intracranial arterial stenosis (ICAS) and analyze its association with different levels of stroke risk and risk factors based on the risk assessment scale for stroke used in China. Methods: A total of 3654 participants who underwent transcranial Doppler ultrasound (TCD) were eligible for inclusion. Information regarding demographic characteristics and risk factors such as alcohol consumption and hypertension was collected through interviews and questionnaires and used to analyze the association of ICAS with different levels of stroke risk and risk factors. Results: The mean age of 501 subjects diagnosed with at least one ICAS was higher than that of participants without ICAS (57.13 ± 9.56 years and 55.52 ± 9.35 years, respectively). After adjusting for confounding factors, gender, education, residence, hypertension and personal history of stroke were associated with ICAS. The odds ratios for ICAS in patients with hypertension and a personal history of stroke were 1.655 [95% confidence interval (CI): 1.341–2.043] and 1.854 (95% CI: 1.371–2.508), respectively. In addition, participants in the low- and moderate-risk stroke groups accounted for an unexpectedly high proportion of individuals with ICAS (up to 38.3%). Results from multivariate analyses indicated that the adjusted odds ratios for ICAS in patients with moderate and high stroke risks versus those with a low stroke risk were 1.603 (95% CI: 1.171–2.195) and 1.612 (95% CI: 1.272–2.042), respectively. Conclusion: The prevalence of ICAS is high in northeast China and increases with the level of stroke risk. However, the proportion of patients with ICAS among those with low and moderate stroke risks should also be noted.